ANALISIS PENGARUH JUMLAH SUDU TERHADAP EFISIENSI TURBIN PELTON DENGAN TEKANAN KONSTAN - Een Tonadi (UNIB Press, 2021)
One of the renewable energy sources that can be used for electricity generation is the Pelton turbine. The purpose of this study was to determine the effect of the number of blades on the efficiency of a Pelton turbine with constant pressure. This research was conducted at the Unihaz mechanical engineering laboratory by varying the number of blades, namely 9 blade turbines and 12 blades. Tests were carried out by giving load gradually to the turbine until the turbine rotor rotation stopped rotating. The results show that in the turbine test with blades 9 the maximum rotation achieved is 698.2 rpm and the maximum rotor rotation is 714.5 rpm at blade 12. Likewise, the torque coefficient and power coefficient achieved by the turbine with 12 are greater when compared to the 9 blades. Meanwhile, the efficiency that can be achieved by turbines with 9 blades is 71% and at 12 blades is 79%. From this it can be concluded that the number of blades affects the rotation, torque coefficient, power coefficient and efficiency of the Pelton turbine with constant pressure.